London 2013, 75th Eage Conference en Exhibition Incorporating SPE Europec 2013
DOI: 10.3997/2214-4609.20130427
|View full text |Cite
|
Sign up to set email alerts
|

4D Seismic Inversion on Continuous Land Seismic Reservoir Monitoring of Thermal EOR

Abstract: A permanent reservoir monitoring system has been installed for Shell at the end of 2010, on a medium heavy-oil onshore field situated in the north-east of The Netherlands, in the context of re-development of oil production by Gravity Assisted Steam Flood. The first challenge was to continuously monitor, with seismic reflection, the lateral and vertical expansion of the steam chest injected in the reservoir during production over more than a year. As the 4D seismic attributes obtained from monitoring fit the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…This method has recently been successfully applied for steam injection monitoring (Michou et al, 2013). However, this requires substantial experimental effort; developing less expensive monitoring techniques is thus desirable.…”
Section: Introductionmentioning
confidence: 99%
“…This method has recently been successfully applied for steam injection monitoring (Michou et al, 2013). However, this requires substantial experimental effort; developing less expensive monitoring techniques is thus desirable.…”
Section: Introductionmentioning
confidence: 99%
“…For example, depending on the mobility (relative permeability divided by viscosity), a waterfront may move typically at a velocity of 0.3–1.5 m/day (Tjetland, Kristiansen and Buer ), whereas hydrocarbon gas, steam or CO 2 fronts can propagate at up to 5 m/day (Michou et al . ). It is observed that in some cases CO 2 propagation can exceed 13 m/day (Lu et al .…”
Section: Seismic Acquisition Versus Production Time‐scalesmentioning
confidence: 97%
“…The most common 4D inversion workflows known to the industry include either a separate inversion of the base and monitor surveys (e.g., Sarkar et al, 2003) or a simultaneous inversion of the base and monitor, as illustrated, for instance, by Michou et al (2013) in the framework of an onshore permanent reservoir monitoring.…”
Section: Time-lapse Inversionmentioning
confidence: 99%